The Prognostic Significance of Hydronephrosis and Role of Ureteric Stenting in Cervical Cancer Patients Treated with Radical Radiation Therapy, Real World Outcomes from a Regional Cancer Centre, South India - Ganesarajah, Selvaluxmy; Jayapaul, Vasanth Cristopher; Madhavan, Ram; Krishnan, Vengada (Asian Pacific Journal of Cancer Care, 2022)
Background: The incidence of renal failure in carcinoma cervix ranges from 14% to 44·2%. The interventional strategies like ureteric stenting and percutaneous nephrostomy can be considered to improve renal function. The primary objective of our study is to analyze the impact of hydroureteronephrosis [HUN] in the outcome of cervical cancer patients treated with radical radiation. The secondary objective is to analyze the role of ureteric stenting to protect the renal function while proceeding with radical radiation. Methods: In this retrospective study, all patients with stage IIIB cervical cancer treated with radical radiation therapy at our institution from January 2010 to December 2019 were included. Results: Among the total 483 stage IIIB patients, 146 patients [30·22%] had hydronephrosis.Thirty eight [26·02%] out of 146 patients with HUN underwent ureteric stenting. The five year overall survival [OS] was 61·4 ± 0·04 % and on subset analysis, overallsurvival was 65·7 ± 0·05 % for patients without HUN and 50·6 ± 0·06 % for patientswith HUN. [P value <0·001]. Among patients with hydronephrosis, those with bilateral hydronephrosis or serum creatinine >1·1 mg/dL have benefitted more from stenting. In this high risk subgroup, the one year overall survival was 65·2 ± 0·11 % and 42·4 ±0·13 % for patients with and without stenting. [p value 0·07]. No major stent related morbidity occurred. Conclusions: Hydronephrosis in cervical cancer patients indicates bad prognosis which results in decreased survival. The presence of hydronephrosis should be redesignated as a separate substage, IIIB2 in future FIGO updates, for better prognostication and treatment recommendations. The relief of obstructive uropathy should be sought out inpatients with serum creatinine levels > 1·1 mg/dL or bilateral hydronephrosis before theinitiation of oncological treatment.